The roles of coaches in optimizing team functioning in curling - Perceptions of high performance coaches and athletes - Collins, J.; Durand-Bush, N. (International Journal of Coaching Science, 2016)
Coaches have been described as teachers, leaders, motivators, managers, and arbitrators (Giges, Petitpas, & Vemacchia, 2004). That said, how coaches fulfill such roles is not well understood. The current study stems from an extensive grounded theory (Charmaz, 2006) research initiative in which factors and strategies contributing to optimal functioning in high performance curling teams were investigated. The purpose of this study was to uncover the various roles of curling coaches in the process of developing high functioning teams based on the perceptions of both coaches and athletes. Participants were members of 19 high performance curling teams (N=78 athletes) and their coaches (N=10). Data were collected from teams of athletes through face-to-face focus group interviews, and from coaches via individual telephone interviews. Results show that coaches played five primary roles: technical/tactical specialist, mediator, manager, facilitator, and motivator. These roles were dependent on athletes` needs as well as both coaches and athletes` personal characteristics and competencies. Coaches and athletes` perceptions regarding these roles sometimes differed, however, both parties reported that coaches sometimes lacked competencies to perform certain roles. Consequently, specific training should be provided to enable coaches to assist athletes in optimizing team functioning in curling.